2021
DOI: 10.3390/jpm11070678
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ventilatory Disorders with Respiratory Symptoms, Physical Activity, and Quality of Life in Subjects with Prior Tuberculosis: A National Database Study in Korea

Abstract: Tuberculosis (TB) survivors experience post-TB lung damage and ventilatory function disorders. However, the proportions of obstructive and restrictive ventilatory disorders as well as normal ventilation among subjects with prior TB are unknown. In addition, the impacts of ventilatory disorder and its severity on respiratory symptoms, physical activity limitations, and the quality of life in subjects with prior TB remain unclear. Subjects who participated in the Korean National Health and Nutritional Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For example, Lee et al have found that the FVC and postbronchodilator FEV1 of patients with chronic air ow obstruction were less than those of COPD patients (P < 0.05) [23]. Furthermore, Yang et al have determined that severe obstructive ventilatory disorders are associated with more respiratory symptoms, and among subjects with prior TB, 29% developed obstructive ventilatory disorders [24]. Abnormal lung function associated with pulmonary TB was observed in 18-94% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al have found that the FVC and postbronchodilator FEV1 of patients with chronic air ow obstruction were less than those of COPD patients (P < 0.05) [23]. Furthermore, Yang et al have determined that severe obstructive ventilatory disorders are associated with more respiratory symptoms, and among subjects with prior TB, 29% developed obstructive ventilatory disorders [24]. Abnormal lung function associated with pulmonary TB was observed in 18-94% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…chest radiography and computed tomography, -spirometry (including bronchodilator response), -plethysmography (assessment of lung volumes), -DLCO (diffusion for carbon oxide), -arterial blood gas analyses (median arterial blood oxygen saturation and mean arterial oxygen partial pressure), -evaluation of the capacity to perform exercise via the six minute walk test (6MWT) or the incremental shuttle walk test (ISWT) [4,31,149,150,[152][153][154][155].…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…In other words, management of possible fungal infections in those individuals could lead to higher rates of candidate identification for future pulmonary rehabilitation programs. Moreover, fibrotic patterns, revealed by chest X-rays, can lead to pain or dyspnea (specific symptoms of restrictive ventilatory pathogenesis) [154,158], further selecting post-TB survivors as possible rehabilitation recipients.…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on age, sex, body mass index (BMI), smoking history, alcohol consumption, marital status, income, area of residence, education, and cardiac symptoms were obtained from the NHANES database. Comorbidities of stroke, asthma, pulmonary tuberculosis, and chronic kidney disease were self-reported based on previous physician diagnoses (10)(11)(12)(13). Chronic obstructive pulmonary disease (COPD) was defined based on pre-bronchodilator forced expiratory volume in 1 s (FEV 1 )/forced vital capacity (FVC) < 0.7 (14).…”
Section: Confounding Variablesmentioning
confidence: 99%